Tailoring of the Structural and Optoelectronic Properties of Zinc-Tin-Oxide Thin Films via Oxygenation Process for Solar Cell Application - Islam M.A.; Rafiq M.K.S.B.; Misran H.; Uzzaman M.A.; Techato K.; Muhammad G.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electronic properties; II-VI semiconductors; Metals; Oxide minerals; Oxygen; Oxygenation; Thin film solar cells; Thin films; Tin oxides; Zinc oxide; Atomic compositions; Compositional variation; Optoelectronic properties; Oxygen incorporation; Solar-cell applications; Thermal annealing process; Uniform microstructure; X-ray diffraction spectrum; Oxide films